An Approach to Voltage Quality Enhancement by Introduction of CWVM for Distribution System - Alok Kumar Shrivastav; Pradip Kumar Sadhu; Ankur Ganguly; Saumen Dhara (Institute of Advanced Engineering and Science, 2016)
This paper presented with problems related with voltage flicker in power system networks. Several international standard issued to control the voltage flicker are briefly described and some important methods to analyse electrical circuits with sinusoidal and non-sinusoidal waveforms are introduced and evaluated. One of these methods – Cockcroft Walton Voltage Multiplier (CWVM) has been used to increase the voltage of a filter, which is also described in this paper as a practical application. The filter can compensate for harmonic currents, power factor, and unbalance voltage. The simulation results using Multisim are presented, showing that good dynamic and steady-state response can be achieved with this approach.